Contratación, administración o uso exclusivo sobre bienes en copropiedad y tutela jurídica de los copropietarios excluidos. Redescubriendo la gestión de negocios ajenos (negotiorum gestio) - León Hilario, Leysser (2023)
Under the Peruvian Civil Code, the exclusive use of a co-owned property that excludes the others co-owners, is sanctioned with the obligation to pay a proportional indemnity to the excluded party. To solve application problems of this rule such as the quantification of the indemnity, with criteria of corrective justice, and not only punitive, it is essential to determine the nature of that remedy, and, by means of the historical-comparative method, revealing its basis, and its interaction with the rights and obligations arising from the management of other people’s affairs (negotiorum gestio).